Cryptocurrencies vs Central Banks' Digital Currencies: The Role of Financial Literacy - L. V. Krylova; I. V. Lukashenko (Финансы: теория и практика)
A bifurcation point has arisen in the transformation of the global monetary and financial system, associated with its further digital transformation: will it be based on private digital currencies like Bitcoin, or on the basis of central bank digital currencies (CBDC)? To a large extent, this depends on the willingness of economic agents to use virtual currencies.The purpose of the study is to explore the factors determining the attitude of economic agents to digital currencies and the impact of financial literacy on using these instruments as an investment object and means of payment.The authors use the following research methods: content analysis, retrospective analysis, methods of comparative cross-country analysis, and empirical research in the form of an online survey of graduate financial students. This study is one of the first to reveal differences in the assessment of their knowledge and readiness to use digital currencies of financial and non-financial students, as well as to confirm an adequate assessment of the risks and opportunities of different types of virtual currencies if students have financial knowledge. The research shows that the situation with the decisionmaking of economic agents on the use of cryptocurrencies and the CBDC differs: in the first case, the initiative comes from the economic agents themselves, who make decisions at their own peril and risk; in the second case, economic agents are confronted with the fact of the existence of the CBDC and the need to use them.The authors conclude that the population’s low financial and digital literacy can create a mental barrier to the use of CBDC, complicating their implementation in national monetary systems. The lack of financial literacy leads to an exaggeration of their knowledge by participants in the cryptocurrency market.